PENGARUH HARGA, KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Haja Avetoe & Lamidi (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
The purpose of this study was to analyze the significance of the effect of price, quality of service and location on consumer purchasing decisions in Dealer Panggung Motor Yamaha Nusukan. To analyze the most dominant variable influence on the Dealer Panggung Motor Yamaha Nusukan. In conclusion, that there is a significant influence price, quality of service and location on consumer purchasing decisions in Dealer Panggung Motor Yamaha Nusukan. Quality of care is the most dominant variable influence on consumer purchase decisions in Dealer Panggung Motor Yamaha Nusukan. Keywords: Price, Quality Service, Location And Consumer Purchasing Decisions.